Arden of Faversham, the authorship problem: Shakespeare, Watson, or Kyd?. (15th October 2021) - Vickers, Brian
Abstract: Arden of Faversham, a play published anonymously in 1592, was for many years attributed to Thomas Kyd. In modern times, it has been claimed that Shakespeare contributed one or more scenes, and in a recent essay in this journal, Gary Taylor argued that Thomas Watson (1555–92) wrote at least one scene. There are several problems with this attribution. As noted elsewhere, Watson was an eminent neo-Latin scholar and no record exists of him ever writing English plays for the Elizabethan theatres. Taylor attributes one 'theatrical work' to him, but this was a welcoming oration that Watson wrote for Queen Elizabeth's visit to the Earl of Hertford at Elvetham in 1591, a one-off event, which does not resemble a play. In this essay, I examine Taylor's use of stylometric evidence. I show that his algorithm is designed to favor Watson, with his small canon, by calculating the number of words per hit. Despite Taylor's repeated dismissal of Kyd's authorship, I point out that his searches of other authors identified thirty-five matching passages with Kyd's plays. Finally, I adduce recently available evidence that strongly confirms Kyd's authorship of the whole play.